SPECIES DIVERSITY OF PULSE BEETLE IN FOUR MAJOR GRAIN LEGUMES IN ANDHRA PRADESH - P. Harika , (The Journal of Research ANGRAU, 2024)
Studies were carried in kharif, 2022 to know the species diversity of pulse beetles infesting  stored grain legumes in Krishna zone of Andhra Pradesh.The pulse beetles were identified as Callosobruchus maculatus and C. chinensis based on their morphological characters. A total of 1391 adults of C. maculatus were observed in blackgram. About 737 and 473 individuals of C. maculatus were recorded in greengram and chickpea, respectively. A total of 566 individuals of C. maculatus and 241 individuals of C. chinensis were found in pigeonpea grains collected from the different storage godowns. The diversity indices for pulse beetle species in pigeonpea were calculated. The Shannon- Wiener index was 2.712, indicating moderate diversity.The species evenness was 0.6273 suggesting that the evenness among the species was zero and the Margalef index was 3.436 indicating relatively high species richness.